2009
DOI: 10.1001/archsurg.2009.190
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Determine Satisfaction With Surgical Treatment of Low-Income Women With Breast Cancer

Abstract: Objective To examine the relationship of overall patient satisfaction with the treatment provided by the surgeon and the consultation process and skills, in low income women undergoing surgical treatment for breast cancer. Design Cross sectional survey. Logistic regression was used to assess the relationship between satisfaction with surgeon treatment and four consultation skills and processes (time spent, listens carefully, explains things in a way you could understand, and shows respect for what you had to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Greater information giving has been associated with greater satisfaction and improved quality of life . In one study, women with BC who had less knowledge regarding their condition reported regret about their treatment decisions .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Greater information giving has been associated with greater satisfaction and improved quality of life . In one study, women with BC who had less knowledge regarding their condition reported regret about their treatment decisions .…”
Section: Discussionmentioning
confidence: 99%
“…Satisfaction with health care providers has been associated with the continued use of health care services, health care provider follow‐up care, better psychological outcomes, and improved quality of life . Better patient‐physician communication is associated with self‐efficacy, adherence, and satisfaction with care …”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer care research with African Americans and Latinas reported lower patient satisfaction related to perceived insensitivity from providers and denied access to care (Ashing-Giwa et al, 2004; Howard et al, 2007; Katz et al, 2005; Mandelblatt et al, 2003). However, a study of racially diverse patients with breast cancer (N = 789) found that most (62%) felt respected by their breast cancer surgeon, although satisfaction was lower among African American women (Thind, Diamant, Liu, & Maly, 2009). None of those studies included an examination of ethnic or cultural identity in the analyses.…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy may be related to variations in the patient navigators' technical skills and the interpersonal relationship between the patient and the patient navigator. Satisfaction with the interpersonal aspects of health care is a key component of patient satisfaction with cancer care . Previous research has indicated that high patient satisfaction with cancer care was associated with multiple patient rankings of navigators in terms of their interpersonal relationship with the navigator …”
Section: Introductionmentioning
confidence: 99%